2016
DOI: 10.1002/uog.17331
|View full text |Cite
|
Sign up to set email alerts
|

Lung and cardiac ultrasound for hemodynamic monitoring of patients with severe pre‐eclampsia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 41 publications
(47 reference statements)
3
70
1
2
Order By: Relevance
“…These findings have also been confirmed by Ambrozic et al. . Conversely, we described one case with tocolytic‐induced pulmonary oedema, who had normal filling pressures but still had bilateral anterior B‐lines and alteration of the pleural line, suggesting a non‐cardiogenic mechanism .…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…These findings have also been confirmed by Ambrozic et al. . Conversely, we described one case with tocolytic‐induced pulmonary oedema, who had normal filling pressures but still had bilateral anterior B‐lines and alteration of the pleural line, suggesting a non‐cardiogenic mechanism .…”
Section: Methodssupporting
confidence: 89%
“…More recently, Ambrozic et al. confirmed these findings; in their cohort only 14% of the women with severe pre‐eclampsia were fluid responsive .…”
Section: Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Ambrozic et al evaluated lung and cardiac ultrasound for assessment of fluid tolerance and fluid responsiveness in severely pre‐eclamptic patients before and after delivery. They found that severe PE is associated with an increase in extravascular lung water, which could in part be caused by disturbed diastolic LV function.…”
Section: Introductionmentioning
confidence: 99%
“…Excess lung water can be identified in severely pre‐eclamptic patients before the appearance of clinical signs by using lung ultrasound. The role of these findings in clinical practice still needs to be determined.…”
Section: Introductionmentioning
confidence: 99%